The EFFECTS OF ANTIVIRAL THERAPEUTIC DRUGS FOR SARS-COV-2 ON TREATMENT OUTCOMES AND CLINICAL PARAMETERS (Eurasian Journal of Ecology, 2024)
The emergence of SARS-CoV-2, the virus responsible for the COVID-19 pandemic, has prompted extensive research into antiviral therapeutic interventions aimed at improving treatment outcomes and clinical parameters. It provides a concise overview of the research conducted in this field, focusing on the impact and significance of various antiviral drugs. To evaluate and summarize the effects of antiviral therapeutic drugs on treatment outcomes and clinical parameters in SARS-CoV-2 patients. By analyzing key studies and trials, it aims to elucidate the efficacy and safety profiles of drugs such as remdesivir, favipiravir, molnupiravir, and Paxlovid in managing COVID-19. The scientific and practical significance of this research lies in its contribution to understanding the role of antiviral drugs in combating SARS-CoV-2 infection. This knowledge is crucial for optimizing treatment strategies and improving patient outcomes during the ongoing pandemic. Methodologically, this research involves reviewing and synthesizing data from reputable studies published in peer-reviewed journals. Key outcomes and clinical parameters assessed include viral clearance, mortality rates, hospitalization duration, and adverse effects associated with antiviral drug administration. The main results and analysis highlight the varying impacts of different antiviral drugs on SARS-CoV-2 treatment outcomes. For instance, remdesivir shows promise in reducing recovery time and mortality, while favipiravir demonstrates enhanced viral clearance but may cause transient liver enzyme elevations. In conclusion, this research underscores the value of antiviral therapeutic drugs in mitigating SARS-CoV-2 infection. The findings contribute to the evolving understanding of COVID-19 treatment strategies and offer insights into optimizing clinical care protocols. The practical significance of these results lies in informing healthcare professionals and policymakers about effective therapeutic options for managing COVID-19 cases, ultimately improving patient care and outcomes. This abstract encapsulates the essential aspects of research on antiviral drugs for SARS-CoV-2, emphasizing its scientific, practical, and methodological significance in advancing our response to the global pandemic.